Membangun Karakter Masyarakat Taat Hukum Perspektif Sosiologi Hukum - Oyo Sunaryo Mukhlas; Nasrudin (STAI Siliwangi Bandung, 2016)
Indonesia is a country of law, the application of law in this country has become the government's commitment from time to time. However, in reality, the application of law in Indonesia faces complex obstacles and problems, one of the contributing factors is allegedly that the level of public awareness of the law is still low. This can be seen from the high level of lawlessness and crime that occurs from time to time. In theory, law enforcement must be supported by three things, namely: legal substance, structure and culture. This means that law enforcement will be effective if it is supported by three elements, namely: the existence of legal rules applied by the government, the existence of legal structures that are realized by the presence of law enforcement officials, and there is a culture or legal culture, namely public awareness to implement the rule of law. This paper tries to analyze the efforts made by the government to foster legal awareness among the public. Among others, by strengthening religious understanding and practice through religious institutionalization and intensification of religious values, strengthening the education system, strengthening economic problems, and implementing reward and funisment systems. However, the effectiveness of the program must continue to be tested with consistency and continuous evaluation.